The tendencies of bioclimatic conditions changes and dynamics occurrence of thermally stimulus weather events in the Polish Baltic coastal zone - Tylkowski, Jacek (Journal of Education, Health and Sport, 2017)
The paper presents the temporal and spatial variability of bioclimatic conditions in the Polish Baltic coast in the 1966-2013 period. The dynamics and trend of bioclimatic changes in the seaside zone are related to the following thermal indicators: the degree of nuisance, thermal sensation, human well-being and thermal stimulus. Proper identification of bioclimatic trends is very important for human health, especially in terms of holiday tourism and spa treatment.